S78 Evalution of an ambulatory pleural service: costs and benefits. (14th November 2013) - Young, RL; Bhatnagar, R; Mason, ZD; Benson, AJ; Hooper, CE; Clive, AO; Zahan-Evans, N; Morley, AJ; Harvey, JE; Medford, ARL; Maskell, NA
Abstract : Background: Outpatient management of undiagnosed pleural effusions is increasing. Payment for managing these patients is usually based on standard outpatient Healthcare Resource Group (HRG) codes. For 2013/14, a new Best Practice Tariff (BPT) of £1534 has been introduced to further disincentivize emergency inpatient management. We audited our service and examined what effects this tariff may have when applied. Methods: Our well-established tertiary pleural service serves a local population of around 540, 000. New patients are seen in a weekly pleural clinic or in a daily respiratory admission avoidance (Hot) clinic, which had standard 2012/13 tariffs of £223 and £334 respectively. The service sees approximately 150 new effusion patients per year in clinic and 3 new patients per week in Hot. Around 50 medical thoracoscopies and 60 indwelling pleural catheter insertions are performed each year. We audited randomly selected patients from our large, prospectively-maintained database. All audited patients were seen as new pleural effusion referrals between 2008 and 2012. Diagnosis was confirmed after a minimum of 12 months' follow-up. Results: 146 patients were audited. Median age 76(range 21–93), 71% male. Final diagnoses were mesothelioma (n = 28, 19%), lung cancer (n = 10, 7%), breast cancer (n = 13, 9%), other cancer (n = 31, 21%), pleural infection (n = 15, 10%), benign pleuritis (n = 11, 8%) and other (n = 38, 26%). 92% of patients avoided direct admission following their initial clinic appointment. 115 patients (79%) underwent ultrasound-guided pleural aspiration at their initial appointment and 63(43%) patients underwent subsequent pleural biopsy. For patients with malignancy, diagnostic sensitivity on first fluid cytology was 27% (adenocarcinoma n = 15, 80%; mesothelioma n = 21, 5%), and 93%(25/27) for medical thoracoscopy biopsy. Histological/cytological diagnosis took a median of 20 days (IQR 10–33) from presentation. There were no significant procedural complications noted (bleeding, pneumothorax, empyema). 97%(58/60) of patients surveyed rated the service as either very good or excellent. Conclusions: Ambulatory management of undiagnosed effusions is efficacious, avoids hospitalisation in the vast majority and is preferred by patients. The 2013/14 pleural effusion BPT promotes admission avoidance by encouraging appropriate outpatient management. Trust reimbursement for practising in this way should facilitate enough resource to enable new pleural services to be established where required.